2023
DOI: 10.1038/s41598-023-29647-0
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning methods and EEG to discriminate aircraft pilot cognitive workload during flight

Abstract: Pilots of aircraft face varying degrees of cognitive workload even during normal flight operations. Periods of low cognitive workload may be followed by periods of high cognitive workload and vice versa. During such changing demands, there exists potential for increased error on behalf of the pilots due to periods of boredom or excessive cognitive task demand. To further understand cognitive workload in aviation, the present study involved collection of electroencephalogram (EEG) data from ten (10) collegiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The only study that demonstrates the impact of COVID-19 on this professional group relates to the risk of SARS-CoV-2 virus infection in small aircraft, which can occur during flights between pilots [ 37 ]. Therefore, in our opinion, the use of quantitative electroencephalography as a method to diagnose the impact of the SARS-CoV-2 virus on the central nervous system of professional pilots represents an innovative approach, as it is the first study conducted on this professional group in which cognitive function disorders have appeared after recovering from the coronavirus [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only study that demonstrates the impact of COVID-19 on this professional group relates to the risk of SARS-CoV-2 virus infection in small aircraft, which can occur during flights between pilots [ 37 ]. Therefore, in our opinion, the use of quantitative electroencephalography as a method to diagnose the impact of the SARS-CoV-2 virus on the central nervous system of professional pilots represents an innovative approach, as it is the first study conducted on this professional group in which cognitive function disorders have appeared after recovering from the coronavirus [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pupil diameter change has previously been associated with Duty Cycle and Aggressiveness derived from stick deflections in VR flight tasks [23]. Recently, EEG data have been implemented in an offline classification of workload of pilots during real flight [36]. Additionally, Kakkos et al [37] have shown that EEG data can be used to classify workload of novice users in low-fidelity VR simulators using machine learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments demonstrated that the proposed method could achieve significant performance. In the field of aviation, in [ 146 ], they proposed using EEG to discriminate aircraft pilot cognitive workload during flight, which achieved an accuracy of 91.67% in classification tasks. Furthermore, in the maritime field, an approach was proposed for assessing mental fatigue based on EEG frequency bands [ 147 ].…”
Section: The Pipeline Of Eeg Signal Analysismentioning
confidence: 99%